Introduction of a new generic synonymy and three newly recorded species of Nolinae (Lepidoptera: Nolidae) from India - Joshi, Rahul; Singh, Navneet; Kuni, Nikhil (Zootaxa, 2020)
A monotypic genus Purenola Qi, László, Ronkay, Bae & Han, 2013 is proposed here as a synonym of the genus Membranola Pellinen (2012). In addition, Leucobaeta hemiphea (Hampson, 1905), Nola infralba Inoue, 1976 and Nola atrocinta Inoue, 1998 are reported for the first time from India. With 13 colour illustrations of adults and genitalia images.